Penerapan Metode Demontrasi Pada Pembelajaran Salat Fardu - Ramadhani, Zelin Desri; Rahman, Rini (Prodi Pendidikan Keagamaan Islam, 2025)
This research aims to develop an effective method for teaching obligatory prayers at the early childhood education level, particularly at Raudhatul Athfal El Azzam. The study evaluates the use of the demonstration method in teaching these prayers. A qualitative descriptive approach was employed, using interviews and observations to gather data on the method's implementation, student responses, and its impact on understanding prayer movements and recitations. The findings revealed that the demonstration method effectively helped students learn prayer procedures. The process began with a video tutorial, followed by a teacher's demonstration, and students taking turns practicing the prayer movements. After one week, joint practice further reinforced their skills. Supporting materials like prayer posters enriched the learning experience, and positive student responses indicated increased understanding and confidence. The study concludes that the demonstration method is successful in teaching obligatory prayers in an engaging and effective manner.